Glucosamine activates intestinal P-glycoprotein inhibiting drug absorption - Qinghua Wu; Qing Wang; Xiaohong Luo; Peng Jin; Ming Jin; Sajid Hussain; Yiming Qi; Junfeng Mo; Yinglan Yu; Hao Shao; Lei Luo (Nature Communications)
Abstract P-glycoprotein (P-gp) is a crucial drug efflux transporter in the gastrointestinal tract, reducing drug uptake and expelling harmful xenobiotics to prevent pathological changes. Current P-gp enhancers primarily increase P-gp expression, requiring 1–3 days, thus missing the critical rescue window for acute poisoning. This study identifies glucosamine (GlcN) as a potent P-gp activator that swiftly enhances drug efflux, significantly reducing drug absorption without altering P-gp expression levels. GlcN directly binds to P-gp, boosting its transport efficiency. Only GlcN with a polymerization degree below 5 can activate P-gp, whereas higher polymerized chitooligosaccharides enhance drug absorption. Additionally, GlcN activation of P-gp has significant implications for cellular metabolism by expelling xenobiotics and metabolic by-products, maintaining cellular homeostasis. Our findings suggest GlcN’s potential as an effective antidote for paraquat poisoning and offer a detoxification strategy. This research provides a foundational understanding for developing improved detoxification agents and metabolic modulators.